Differences in maladaptive schemas between patients suffering from chronic and acute posttraumatic stress disorder and healthy controls - Ahmadian A (Dove Medical Press, 2015)
Alireza Ahmadian,1,2 Jafar Mirzaee,1 Maryam Omidbeygi,1 Edith Holsboer-Trachsler,3 Serge Brand3,41Department of Psychology, Kharazmi University, 2Sadr Psychiatric Hospital, Janbazan Medical and Engineering Research Center (JMERC), Tehran, Iran; 3Psychiatric Clinics of the University of Basel, Center for Affective, Stress and Sleep Disorders, 4Department of Sport, Exercise and Health, Sport Science Section, University of Basel, Basel, Switzerland Background: War, as a stressor event, has a variety of acute and chronic negative consequences, such as posttraumatic stress disorder (PTSD). In this context, early maladaptive schema-based problems in PTSD have recently become an important research area. The aim of this study was to assess early maladaptive schemas in patients with acute and chronic PTSD.Method: Using available sampling methods and diagnostic criteria, 30 patients with chronic PTSD, 30 patients with acute PTSD, and 30 normal military personnel who were matched in terms of age and wartime experience were selected and assessed with the Young Schema Questionnaire-Long Form, Beck Depression Inventory second version (BDI-II), the Beck Anxiety Inventory (BAI), and the Impact of Events Scale (IES).Results: Both acute and chronic PTSD patients, when compared with normal military personnel, had higher scores for all early maladaptive schemas. Additionally, veterans suffering from chronic PTSD, as compared with veterans suffering from acute PTSD and veterans without PTSD, reported more impaired schemas related, for instance, to Self-Control, Social Isolation, and Vulnerability to Harm and Illness.Discussion: The results of the present study have significant preventative, diagnostic, clinical, research, and educational implications with respect to PTSD. Keywords: veterans, PTSD, depression, anxiety